Sleep problems in autism spectrum disorders: A comparison to sleep in typically developing children using actigraphy, diaries and questionnaires. (November 2019) - Surtees, Andrew D.R.; Richards, Caroline; Clarkson, Emma L.; Heald, Mary; Trickett, Jayne; Denyer, Hayley; Crawford, Hayley; Oliver, Chris
Highlights: Sleep problems are commonly reported in children with Autism Spectrum Disorders. Sleep in a group of children with Autism Spectrum Disorders was compared to a matched control group. No differences were found using actigraphy or parent diaries. Large differences were evident on questionnaire measures. Children with Autism Spectrum Disorders had high rates of parasomnias, sleep onset problems and day-time sleepiness. Abstract: Background: It has been reported widely that children with Autism Spectrum Disorders (ASD) are more likely to experience sleep problems than children without ASD. Sleep problems are among the most prevalent comorbid difficulties with ASD. The current study aimed to use multiple methods to describe these difficulties. Method: Sleep of sixteen children with ASD and a parentally-reported sleep problem was compared to the sleep of a matched group of children without ASD. Seven nights of actigraphy data were collected for both groups, alongside sleep diaries and questionnaires. Results: No group differences were identified through actigraphy or diary measures. Questionnaire data confirmed that the children with ASD had a higher prevalence of sleep problems. Significant differences were noted in problems with parasomnias (a frequent problem for 79% of the children with ASD), sleep onset (43%) and day-time sleepiness (64%). Conclusions: Multi-method assessment is vital in understanding sleep problems in children with ASD. Broad estimates of quantity of sleep do not necessarily describe the difficulties experienced. Using questionnaires in addition to objective measurement may be a means to understand sleep problems in children with ASD and to an improved understanding of their impact.